Erratum of "A Hermitian analogue of the Morita theorems". Issue 2 (29th September 2020) - Dasgupta, Bhanumati; Dasgupta, Soura
Abstract: In 'A Hermitian analogue of the Morita theorems' by Dasgupta and Dasgupta, we proved a Hermitian Morita II. There is an error in the proof of Proposition 3.1 which nullifies the paper.